Race, space, and riots in Chicago, New York, and Los Angeles - Abu-Lughod, Janet L. (Oxford : Oxford University Press, 2007)
Janet Abu-Lughod weaves together detailed narratives of major riots with the changing contexts in which they have occurred to show how urban space, political regimes, and economic conditions - not simply an abstract 'race conflict' - all structure the nature and extent of urban rebellions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Race riots -- United States -- History -- 20th century; African Americans -- Social conditions -- 20th century; United States -- Race relations